2000
DOI: 10.1002/1099-1395(200005)13:5<306::aid-poc291>3.3.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

J. Phys. Org. Chem. 2000; 13:203–207, “Solvolysis of 2‐aryl‐2‐adamantyl p‐nitrobenzoates and some tertiary benzylic p‐nitrobenzoates. YBnOPNB and YxBnOPNB scales”, by K.‐T Liu et al.

Abstract: Solvolysis rate constants for a number of tertiary benzylic p-nitrobenzoate esters in a wide range of solvents were measured. New scales of solvent ionizing power for Grunwald-Winstein-type correlation analyses, Y BnOPNB from 2-phenyl-2-adamantyl p-nitrobenzoate and Y xBnOPNB from 2-(6-methoxy-2-naphthyl)-2-adamantyl p-nitrobenzoate, were developed for the mechanistic study of solvent effects on the solvolytic reactivity of benzylic p-nitrobenzoates. The excellent linear log k -Y BnOPNB plot for 2-(4-methylphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…By using the reported kinetics of solvolysis (see the Supporting Information, part 7),– together with the N f and s f parameters for Br − and Cl − in various solvent mixtures, plots of (log k ion )/ s f against N f were constructed (Figure ) and thus gave access to the electrofugality parameters E f of the five phenylfluorenyls 2(b–f) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…By using the reported kinetics of solvolysis (see the Supporting Information, part 7),– together with the N f and s f parameters for Br − and Cl − in various solvent mixtures, plots of (log k ion )/ s f against N f were constructed (Figure ) and thus gave access to the electrofugality parameters E f of the five phenylfluorenyls 2(b–f) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the existence and location of the critical point is still unknown, we need an algorithm which can be applied beyond the small chemical potential region. This is one of the motivations of our studies via the canonical ensemble approach [20,21,22,23,24].…”
Section: Pos(lat2009)011mentioning
confidence: 99%
“…To generate this ensemble a candidate configuration is "proposed" by the standard Hybrid Monte Carlo algorithm [38,39,40,41], then an accept/reject step is used to correct the weight. We note that the accept/reject step is based on the determinant ratio which alleviates the fluctuation problem [42,22,25] and enhances the acceptance rate [26].…”
Section: Pos(lat2009)011mentioning
confidence: 99%
“…This class of materials has been extensively studied for their potential applications in actuation, energy conversion and charge storage [1][2][3][4]. However, up to now all the investigations were performed on polycrystalline PLZST samples [5][6][7][8][9][10], and their practical use was limited to sintered ceramics consisting of randomly oriented crystal grains. If the appropriate axis is utilized, single crystals generally have superior properties than the polycrystalline ceramics, for example PMN-PT [11][12][13], PZN-PT [14][15][16] However, few studies have reported PLZST single crystal growth to our knowledge.…”
Section: Introductionmentioning
confidence: 99%